Prevention of the attention deficit hyperactivity disorder in children through speed reading - Vasileva L. L. (Humanitarian, 2018)
in recent years, attention deficit hyperactivity disorder has become not only a problem in the organization of the educational process, but it is also becoming a public problem, since children of school and preschool age hardly learn and retain information. The volume of information has increased many times. Our ability to work with it, translate into a practical plane, remains at the same level. The intensive development of information technologies in conjunction with the development of scientific progress leads to the need to improve the learning mechanism. Adaptive technologies of intellectual abilities development of a person take into account the natural interests of people of different age groups, allow to optimize intellectual processes, the recoding of information teaches a person to think. The better the brain encodes information, the better it remembers. The main characteristics of adaptive technologies for the development of a person's intellectual abilities through a single path – speed reading – are considered in the context of practical and applied recommendations that allow the learner to master various types of reading.
Keywords: тренинг; интеллектуальные способности; training; intellectual abilities; синдром дефицита внимания и гиперактивности; скорочтение; speed reading; адаптивные технологии; скорость мыслительных процессов; мозговые структуры; информативный путь обучения; трансформативный путь обучения; attention deficit hyperactivity disorder; adaptive technologies; speed of cognitive processes; brain structure; informative learning path; transformative learning path